KONSEPSI ISLAM TENTANG KERJA Rekonstruksi Terhadap Pemahaman Kerja Seorang Muslim - Armansyah Walian Walian (Pusat Studi Gender dan Anak Universitas Islam Negeri Raden fatah palembang, 2012)
Man as his personal nature will require food, making a living requires sustenance in all times and circumstances, since childhood to adulthood and so forth until you reach old age though, and created a wide range of things on this earth is for the purposes of human usefully warranty provision of sustenance him.